Pengaruh Lingkungan Sosial, Perilaku Konsumen Dan Persepsi Terhadap Minat Berwirausaha Mahasiswa BSI Yogyakarta - Atun Yulianto (Universitas Bina Sarana Informatika, 2014)
The small interest of students BSI Yogyakarta in entrepreneurship became an the problems which is the focus of this study. This situation is indicated by the least amount of students the following sort course entrepreneur that ever into a work program BSI Entrepreneur Center. Based on this, researchers attempted to knowing several factors such as the social environment, consumer behavior and perception against student interest in entrepreneurship. The method used is quantitative descriptive with multiple linear regression analysis for knowing effect independent variables against the dependent variable either partially or simultaneously. T tests were done partially for social environment and consumer behavior no effect against the interest of students in entrepreneurship. Perception as an independent variable last as measured by t test showed significant effect against the interest of students in entrepreneurship. While the simultaneously based on the results of F test showed the significant influence between variable social environment, consumer behavior and perception simultaneously against interest of BSI Yogyakarta students in entrepreneurship. Keywords: socialenvironment, consumer behavior, perceptions